2009
DOI: 10.1057/fp.2009.29
|View full text |Cite
|
Sign up to set email alerts
|

Europe: The quiet superpower

Abstract: This article challenges the conventional view that Europe's global influence is declining. Since 1989 realists have predicted Europe's demise, as well as greater intra-European and transatlantic conflict. The reverse has occurred. This outcome suggests the superior predictive power of liberal international relations theory, which stresses the importance of the varied national interests of states, reflecting specific social coalitions, patterns of global interdependence and domestic institutions. According to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 19 publications
0
36
0
2
Order By: Relevance
“…Numerous studies, particularly in the last two decades, offered different characterisations and depictions of the EU's international role, contribution and identity, focusing on the different facets of its external relations -the EU as a (vanishing) mediator (Nicolaïdis, 2004), a global conflict manager (Whitman, Wolff, 2012), a Kantian power (Kagan, 2004), an ethical power (Aggestam, 2008), a civilian or civilising power (Duchêne, 1972;Sjursen, 2006) and a quiet superpower (Moravcsik, 2002), among others. These depictions often approach the EU's identity as a determinant of its foreign policy behaviour and "the EU's role as an international actor and its international identity are considered a function of the significance of the EU and its member states in international affairs and of the effectiveness of its policy practice" (Sedelmeier, 2004: 125).…”
Section: Conceptualising the Eu As A Normative Powermentioning
confidence: 99%
“…Numerous studies, particularly in the last two decades, offered different characterisations and depictions of the EU's international role, contribution and identity, focusing on the different facets of its external relations -the EU as a (vanishing) mediator (Nicolaïdis, 2004), a global conflict manager (Whitman, Wolff, 2012), a Kantian power (Kagan, 2004), an ethical power (Aggestam, 2008), a civilian or civilising power (Duchêne, 1972;Sjursen, 2006) and a quiet superpower (Moravcsik, 2002), among others. These depictions often approach the EU's identity as a determinant of its foreign policy behaviour and "the EU's role as an international actor and its international identity are considered a function of the significance of the EU and its member states in international affairs and of the effectiveness of its policy practice" (Sedelmeier, 2004: 125).…”
Section: Conceptualising the Eu As A Normative Powermentioning
confidence: 99%
“…EUs militaermakt er saerdeles begrenset av manglende vilje til samordning. En mulig sympatisk holdning ovenfor unionens militaere kapabiliteter ville vaere å bedømme den ut ifra dens potensiale, heller enn dens nåvaerende evne og vilje Á da er EU en supermakt (Moravcsik 2009). …”
Section: Norge Og Den Integrasjonsvillige Habitusunclassified
“…Neorealists such as Waltz predicted that the only way in which the EU could achieve a foreign policy worthy of the name would be if it became a state, that is, if the federal project were compieted (Waitz, ZOOO).Hyde-Price (Z008) concluded that the polarity structure and lack of military resources meant that the EV was turning into a 'tragic power' with its attempt to build a common foreign policy that was doomed to fail. Liberals, from intergovernmentalists such as Moravcsik labelling the EV the (quiet superpower' (Moravcsik, 2010) to institutionalists such as Koenig-Archibugi (Z004), argued that there was potential for developing a common European foreign policy, but that it would (and should) remain intergovernmental (Wagner, 2003). Against this, constructivists and reflectivists claimed that the EU would indeed be -or already was -a power in the world (Manners, ZOOZ;Ruggie, 1998;Sjursen, Z006).…”
Section: Theorising the Eu's Diplomatic Service 19mentioning
confidence: 99%